Review of pig health and welfare surveillance data sources in England and Wales. (16th March 2019) - Smith, Richard P; Correia‐Gomes, Carla; Williamson, Susanna; Marier, Elizabeth A; Gilson, Daniel; Tongue, Sue C
Abstract : The capability to set baselines and monitor trends of health and welfare conditions is an important requirement for livestock industries in order to maintain economic competitiveness and sustainability. Monitoring schemes evaluate the relative importance of conditions so that: appropriate actions can be determined, prioritised and implemented; new and (re)emerging conditions can be promptly detected and the effectiveness of any actions can be measured. In 2011, the national pig levy board published a strategy document highlighting health and welfare conditions of importance to the pig industry that were to be targeted for control. In this study, existing schemes that could be used to monitor or set baselines for these conditions in pigs were reviewed, in order to evaluate their suitability for this purpose, using a standardised surveillance evaluation framework (SERVAL). The schemes included: government‐funded surveillance of endemic and exotic disease and pig welfare; industry surveillance of endemic diseases; regional schemes for improving pig health; national accreditation schemes and information collected by retailers, private veterinary practices and private laboratories. The evaluation of each scheme highlights its capability to monitor any of the targeted conditions. This study identifies the biases, strengths and gaps in each scheme and provides discussion of opportunities for future development.